Role Of Artificial Intelligence in Forensic Odontology: A Review - Khandelwal, Sourabh; Srivastava, Rajeev; Dave, Mahendra; Jain, Ankush; Bais, Kruti; Shrivastav, Sarthak (Journal of Neonatal Surgery, 2025)
Forensic odontology is a specialized branch of dentistry dealing with the identification of individuals through dental evidence for investigation or legal proceedings. Traditionally, maintaining and matching dental records and radiographs, bite mark analysis, age estimation, and gender estimation were done manually, which was time-consuming and prone to errors. However, the introduction of artificial intelligence (AI) is a game changer in this field, addressing the challenges faced by manual methods. It has opened the possibilities of more precise, accurate, reliable, and efficient identification and reduced subjectivity. However, challenges regarding ethical aspects, data privacy and the need for standardization have to be addressed. This review emphasizes the significant role of AI in enhancing forensic odontology and its potential to transform this field